Analisis Multidisipliner terhadap Fenomena Pemberian Pinjaman Online pada Anak Muda: Dampak, Penyebab, dan Solusi - Muhammad Khozin Ahyar; Angga Hergastyasmawan; Fitri Wulandari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The presence of online loans provides new hope for economic development in Indonesia. Online loans is a way for business owners to obtain capital. Online loans offer various simplicity for MSMEs who want to apply for loans, they can get loans quickly using easy conditions, disbursement of funds quickly, and a flexible repayment process. One of the conditions that are not provide in the banking industry is easy terms and loans without collateral. This is a good news for MSME owner who need capital and do not have valuable assets to use as collateral. It is not only the general public who use online loan services but also young people, apart from not requiring administrative requirements and guarantees like banks in general, the process is also fast. However, you need to be careful in using this online loan, because it has two sides. Do not let what is expected is a profit in the form of fund assistance, even a loss due to payment or even pressure from collectors when it is due. According to data from the Financial Services Authority (OJK) there are around 219,824 youth under 19 who are active loan borrowers. The circulation of loan money is also quite large with a total loan of IDR 206.9 billion. Young online borrowers, who are considered to still not have many urgent needs already had the power to borrow from this loan, this is considered very harm. The phenomenon of the rise of this loan is increasingly troubling the community. This system is considered to be damaging the financial digitalization ecosystem which previously benefited the community, instead it has lost tens or even hundreds of millions of rupiah.